PEX5, the Shuttling Import Receptor for Peroxisomal Matrix Proteins, Is a Redox‐Sensitive Protein. (31st October 2013) - Apanasets, Oksana; Grou, Cláudia P.; Van Veldhoven, Paul P.; Brees, Chantal; Wang, Bo; Nordgren, Marcus; Dodt, Gabriele; Azevedo, Jorge E.; Fransen, Marc
<x xml:space="preserve">Abstract</x> Mounting evidence suggests that oxidative stress impairs peroxisomal matrix protein import. This study provides direct evidence that the import of PTS1 matrix proteins into peroxisomes is indeed a redox‐regulated process, and that this redox‐sensitivity is mediated by PEX5, the shuttling receptor for PTS1 proteins. In addition, it demonstrates that Cys11 of human PEX5 functions as a redox switch that modulates PEX5 activity in response to intracellular oxidative stress, most likely by modulating its monoubiquitination at the peroxisomal membrane. <boxed-text content-type="graphic" id="tra12129-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>